Belarusian Healthcare Professionals' Views on Monkeypox and Vaccine Hesitancy - Riad, Abanoub; Rybakova, Nadzeya; Dubatouka, Nadzeya; Zankevich, Ina; Klugar, Miloslav; Koščík, Michal; Drobov, Anton (Vaccines, 2023)
BACKGROUND: Despite the low transmission risk of Monkeypox (mpox) in Belarus, this study is vital as it contributes to our understanding of vaccine hesitancy among healthcare professionals (HCPs). It aims to assess vaccination perceptions and evaluate the willingness to pay for the vaccine among Belarusian HCPs, thereby enhancing pandemic preparedness. METHODS: in October 2022, a cross-sectional survey-based study was conducted among Belarusian HCPs using a self-administered questionnaire (SAQ). Invitations were disseminated via social media platforms using a snowball sampling method. The SAQ encompassed various categories, including sociodemographic details, medical history, sources of mpox information, perceived and factual mpox knowledge, and perceptions of the mpox vaccine according to the health belief model (HBM), mpox vaccine acceptance and willingness to pay (WTP). RESULTS: while a large proportion of respondents had good knowledge of mpox epidemiology and its clinical manifestations, their awareness of available vaccines and treatment options was limited. Consequently, a significant correlation was found between the history of influenza vaccination and mpox-related knowledge. Furthermore, the study showed that just over half of the participants (51.4%) were willing to receive the mpox vaccine if offered for free, safely, and effectively, with their decision largely influenced by perceived benefits (Spearman's rho = 0.451) and cues to action (Spearman's rho = 0.349). However, a considerable degree of hesitancy (30.6%) and resistance (18.1%) towards the mpox vaccine was observed, underscoring the need for targeted interventions to address these issues. CONCLUSIONS: this study highlights a significant knowledge gap among Belarusian HCPs about mpox vaccines and treatments, despite a general awareness of the disease's epidemiology and symptoms, and it underscores the need for targeted interventions to enhance mpox knowledge and vaccine acceptance.
Keywords: cross-sectional studies; disease outbreaks; monkeypox; health belief model; smallpox vaccine; health personnel; Republic of Belarus; vaccination hesitancy; knowledge